The Influence of Principal Supportive Leadership and Work Climate on Teacher Job Satisfaction: A Regression Analysis Supporting SDG 4 on Quality Education - Rismawati; Ahmad Sabandi; Irsyad; Sulastri (Postgraduate, University of Mataram, 2026)
Teacher job satisfaction (TJS) is a pivotal determinant of academic quality, influencing teachers' motivation, commitment, and professional performance. This study examined the influence of Principal Supportive Leadership (PSL) and Teacher Work Climate (TWC) on TJS among public junior high school teachers in a city in West Sumatra, Indonesia. A quantitative explanatory design with a survey method was employed. Using the Slovin formula and proportionate stratified random sampling, 330 teachers were selected from a population of 1,898. Data were collected using self-report questionnaires utilizing a five-point Likert scale and analyzed through descriptive statistics, simple linear regression, and multiple linear regression, following classical assumption tests (normality, linearity, and multicollinearity). Results showed that PSL had a significant positive influence on TJS, and TWC also significantly influenced TJS. PSL and TWC simultaneously had a significant positive influence on TJS. These findings indicate that supportive leadership and a positive work climate are complementary factors that enhance teacher job satisfaction. This study contributes empirical evidence to educational leadership research. It offers practical implications for school heads and policymakers in fostering leadership practices and organizational climates that support teacher well-being and sustainable school improvement.